SKEMA PUBLIC PRIVATE PARTNERSHIP (PPP) UNTUK MENARIK KETERLIBATAN INVESTOR ASING DALAM PROYEK BANDARA KOMODO - Vanesya Putri Angelia (2021)
This study aims to see how the Public-Private Partnership (PPP) scheme can be used as an innovation for funding transportation infrastructure development and an attraction for foreign investors to get involved. The selection of Labuan Bajo as one of the super-priority tourism destinations presents the need to develop Komodo Airport, which is the main entry point for tourists to the Labuan Bajo area to accommodate the increasing flow of tourists. This study uses an international cooperation theory, the concept of Public-Private Partnership (PPP) and Foreign Direct Investment (FDI) with the use of qualitative methods in the analysis process to explain descriptive form regarding the reasons for choosing the PPP scheme, the agreed form of cooperation, and the reasons for choosing PT. Cinta Airport Flores as the implementing business entity in the Komodo Airport project. In this study, the researchers found that the PPP cooperation scheme is the most effective scheme related to project funding and how the government's efforts to attract investors, especially foreign investors, are involved in the Komodo Airport project.